2018
DOI: 10.1007/s00436-018-5898-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and molecular characterization of Clinostomum complanatum (Trematoda: Clinostomidae) in freshwater fishes caught from Turkey

Abstract: The metacercariae of Clinostomum species which known as yellow grubs have zoonotic potential by infecting humans. In the present study, a total of 403 freshwater fish specimens belonging to different genera from Central Anatolia Region of Turkey were examined for yellow grub metacercariae infections. Only three specimens belonging to Squalius cephalus were found to be infected with metacercariae with a prevalence on this host species of 2.4% and an overall prevalence of 0.7%. All the metacercariae were morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
2
9
0
1
Order By: Relevance
“…The morphological characteristics of Clinostomum sp., Euclinostomum sp., Dilostomatid sp., the third larval stage of Contracaecum sp. and A. tilapiae reported in the present study are similar to previous descriptions (Ahmad et al, 2017;Bazh & Hamouda, 2019;Caffara et al, 2014;El-Shahawy et al 2017;Hamouda, 2014;Simsek et al, 2018;Taher, 2009;Younis et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The morphological characteristics of Clinostomum sp., Euclinostomum sp., Dilostomatid sp., the third larval stage of Contracaecum sp. and A. tilapiae reported in the present study are similar to previous descriptions (Ahmad et al, 2017;Bazh & Hamouda, 2019;Caffara et al, 2014;El-Shahawy et al 2017;Hamouda, 2014;Simsek et al, 2018;Taher, 2009;Younis et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The current study also found that there was morphological intraspecific diversity in C. complanatum. Previous researchers also experienced the same problems in the identification of the larval (metacercariae) stage which has less morphological characteristics than adults [24]. Our data also supported that there was morphological intraspecific diversity in C. complanatum, highlighting the utility of molecular approaches about C. complanatum.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, we also found that the low level of variation (within 2%) in ITS between Clinostomum species (C. complanatum, C. cutaneum, C. phalacrocoracis) and this may not be sufficient for discriminating species of Clinostomum without morphological support. Even the species described based on unreliable characters may turn out to be genetically distinct and valid, particularly in cases where types were obtained in different biogeographic regions [24]. Meanwhile, the CO1 sequences of a Myanmar isolate were not correctly matched with those of Clinostomum species (less than 89% identity).…”
Section: Discussionmentioning
confidence: 95%
“…Precise identification of parasite species is more valuable especially in those concerns with the treatment and control of the parasitic infections demonstrated by Moszczynska et al (2009). Due to the difficulties in morphological identification, molecular methods have become useful and popular to distinguish morphologically similar species, and identify species at any developmental stage of parasites demonstrated by Simsek et al (2018). In recent years, mt-COI sequence analyses combined with morphological definition have been successfully utilized to identify and redefine trematode species as previously described by Gustinelli et al (2010), Caffara et al (2011 and Wang et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, significant taxonomic changes of Clinostomum species have been achieved using combined morphologic and molecular approaches to resolve the problem associated with the morphological intraspecific diversity and similarities. Propably, many Clinostomum species have not been identified or described precisely because of the lack of data in regard to the existing species in this genus (Steenkiste et al, 2015;Simsek et al, 2018).…”
Section: Introductionmentioning
confidence: 99%